Carbonatação acelerada em concretos com adição de cinzas de lodo de estação de tratamento de água - Adorna, Diego da Luz (2016)
Carbonation is a natural phenomenon for concrete structures and occurs due to the reaction between CO2, which is concentrated in the environment, and Ca(OH)2, which is present in the cementitious matrix. Carbonation reaction reduces the pH of the concrete and causes the destruction of the passivation layer, which surrounds the steel armor, leaving it vulnerable to the process of corrosion. In this study, was investigated the performance against the carbonation of concrete with the addition of water treatment plant sludge ashes, in concentrations of 5%, 10%, 15%, 20%, 25% and 30% replacing Portland cement, as well as a reference blend without mineral admixtures. All mixtures were molded with three w/b ratios (0.35; 0.50 and 0.65) and with two periods of wet cure (three and seven days). Concrete specimens underwent preconditioning according to RILEM TC 116-PCD, targeting the moisture balance (75% ± 2%) in an aerial environment with constant temperature (23° C ± 2° C) and uniform moisture distribution. Afterwards, specimens were forwarded to a carbonation chamber, with humidity (75 ± 2%), temperature (23°C ± 2° C) and CO2 concentration (3%) duly regulated. Specimens were tested after 4, 8, 12 and 16 weeks of CO2 exposure through phenolphthalein spraying, the depths of carbonation is obtained and, therefore, the carbonation coefficients. Results revealed that the incorporation of water treatment plant sludge ashes into concrete leads to increases in its carbonation, in all mixtures investigated. Comparisons with the results for Porosimetry by Mercury Intrusion and Thermogravimetry enable attribute this effect to the microstructural change and decrease of alkalinity of the mixture with addition of sludge ash. Through an analysis of equal resistance, it was found that concrete with addition of sludge ash water treatment are feasible, from the point of view of carbonation's lifespan, only to higher strength levels.